The role of self-regulation as an intervening variable in the influence of self-efficacy on the learning outcomes of Islamic religious education - Rahman, Ulfiani; Idham; Salman, Ibnu; Qardawi Hamzah, Muh. (Edelweiss Applied Science and Technology, 2024)
Low learning outcomes were observed among some high school students. Psychologically, this issue is influenced by self-efficacy and self-regulation, which students also lack. Therefore, this research aims to examine the influence of self-efficacy on learning outcomes with self-regulation as an intervening variable. This research involved 600 students from elite public high schools in Sinjai, South Sulawesi, Indonesia. School selection was carried out by random sampling across Sinjai. Data were collected through self-efficacy and self-regulation questionnaires as well as learning outcome assessments. Data were analyzed using descriptive statistics and SEM methods. The research results show that self-efficacy does not have a significant effect on learning outcomes (p-value=0.761), but self-efficacy has a significant effect on self-regulation (p-value=0.000). Meanwhile, self-regulation has a significant direct effect on learning outcomes (p-value=0.005). Self-efficacy significantly affects learning outcomes with self-regulation as an intervening variable (p-value=0.017). The goodness of fit indicators are R^2 and SRMR. R^2 for learning outcomes and self-regulation are 0.68 and 0.27, respectively, and the model’s SRMR score is 0.09. This research emphasizes the importance of self-regulation and self-efficacy in improving learning outcomes.